High-Performance Liquid Chromatography with DAD Detection for the Determination of Cannabinoids in Commercial Veterinary CBD Oil - Zehra Hajrulai-Musliu; Elizabeta Dimitreska Stojkovikj; Dimitar Gusheski; Dea Musliu; Daniel Velkovski (Pharmacy)
The study highlights the need for quality control in evaluating medicinal plant products, especially CBD oils, before market release. Due to varying regulatory requirements, product labeling can sometimes be misleading, especially regarding cannabinoid concentrations such as CBD and THC. This research focused on developing a validated high-performance liquid chromatography (HPLC) method for accurately identifying and quantifying key cannabinoids in Commercial Veterinary CBD Oil. The main compounds identified included Cannabidivarin (CBDV), Cannabidiolic Acid (CBD-A), Cannabigerolic Acid (CBG-A), Cannabigerol (CBG), Cannabidiol (CBD), Tetrahydrocannabivarin (THCV), Cannabinol (CBN), ∆9-Tetrahydrocannabinol (d9-THC) ∆8-Tetrahydrocannabinol (d8-THC), Cannabicyclol (CBL), Cannabichromene (CBC), and Tetrahydrocannabinolic Acid (THCA), determined in line with the International Conference on Harmonization’s (ICH) guidelines. The method was validated for linearity, accuracy, precision, limit of detection (LOD), and limit of quantitation (LOQ). It was determined to be linear, with a correlation coefficient (R²) > 0.999. The LOD and LOQ values calculated from the calibration curve ranged from 0.05 to 0.13 and 0.50 to 0.61 µg/mL, respectively. The method also exhibited acceptable precision, with relative standard deviation values lower than or equal to 2%. The method’s accuracy was assessed through recovery percentages and fell within an acceptable range of 98–102 if the RSD was 2%. This study’s rigorous methodology and comprehensive findings significantly contribute to cannabinoid analysis. This validated protocol was used to analyze cannabinoids in 14 commercial veterinary CBD oil products from the Republic of North Macedonia. The performance parameters demonstrated that the method is reliable for quantitatively measuring cannabinoids in CBD oil. The analysis showed that the cannabinoid levels in the products were consistent with the manufacturers’ declared specifications, with no significant discrepancies in labeling.